Correction: Seifalian et al. A Novel Graphene-Based Nanomaterial for the Development of a Pelvic Implant to Treat Pelvic Organ Prolapse. J. Funct. Biomater. 2024, 15, 351 - Amelia Seifalian; Alex Digesu; Vik Khullar (Journal of Functional Biomaterials, 2025)
In the original publication [...]